Optimalisasi Kreativitas, Kedisisiplinan, dan Karakter Islami Siswa melalui Pelatihan Dasar Menggambar sebagai Media Pembelajaran Interaktif - Muhammad Rifki Alfareza; Prabu Janoko Proboputro; Evi Susilawati; Siti Nurlailatul Qodriah; Misbahul Munir; Farhan Alghifari Robbani Kurniawan; Winda Aqielah Izzatul Mazaya; Mirza Saleem Ahmad; Moch Azzam Falih; Irma Novida (Forum Kerjasama Pendidikan Tinggi, 2026)
This community service program was motivated by the low level of Islamic character, learning discipline, and creativity among elementary school students, as reflected in their lack of learning concentration, frequent joking during classroom activities, and unsatisfactory academic achievement. These conditions indicate the need for more innovative, participatory, and enjoyable learning strategies to improve students' engagement in the learning process. This program aimed to optimize students' Islamic character, discipline, and creativity through basic drawing training as an interactive learning medium. The program was conducted at SD Islam Ruhul Amin from April 16 to May 22, 2026, involving 20 students from grades one to six. The implementation method consisted of needs assessment, coordination with the school, program planning, basic drawing training, delivery of Islamic character education through audiovisual media, drawing practice, mentoring, and evaluation using observation, interviews, simple questionnaires, and documentation. The results showed that students demonstrated high attendance and enthusiasm throughout the program. Most participants were able to follow drawing instructions, produce basic shapes correctly, and showed greater confidence in asking questions and presenting their work. The program also increased student participation through practical and collaborative learning activities. However, improvements in Islamic character and learning discipline were not yet optimal because several students still tended to joke with their classmates and had difficulty maintaining consistent learning focus. The results of school examination mentoring also indicated that students' academic achievement remained below the expected standard and therefore required continuous guidance. In addition, the planned renovation of the school building limited the implementation of several follow-up activities. Overall, the basic drawing training positively contributed to improving students' creativity, participation, and self-confidence. Nevertheless, strengthening Islamic character and discipline requires continuous habituation through collaboration among schools, teachers, parents, and higher education institutions to achieve sustainable outcomes.